THU0408 Characteristics of mild to moderate lung disease in systemic sclerosis and impact of survival; data from the population-based, nationwide norwegian cohort. (12th June 2018) - Fretheim, H.; Seip, M.; Halse, A.-K.; Bitter, H.; Wallenius, M.; Aaløkken, M.; Garen, T.; Midtvedt, Ø.; Molberg, Ø.; Hoffmann-Vold, A.-M.
Abstract : Background: In systemic sclerosis (SSc) it is well-documented that severe interstitial lung disease (ILD), defined as an extent of lung fibrosis >20% on high resolution computed tomography (HRCT) is strongly associated with male gender, anti-topoisomerase antibody (ATA), diffuse cutaneous (dc) form of disease and decreased survival. Much less is, however, known about the disease characteristics and impact of less lung involvement. A possible explanation might be the selected nature of many hitherto investigated SSc cohorts. In an era with novel treatment options, and multiple ongoing clinical trials, it is important to gain natural history knowledge on the whole spectre of lung involvement in systemic sclerosis. Objectives: Characterise the SSc patients with mild to moderate ILD, defined as 1%–10% extent of lung fibrosis on HRCT in the population based nationwide Norwegian SSc cohort and assess the impact of this ILD form on survival. Methods: The Norwegian, nationwide SSc (Nor-SSc) study cohort included all adult SSc patients who were resident in Norway between 01.01.2000–01.01.2013 and met the classification criteria for SSc. Detailed electronic patient journal review was performed in all patients to assess demographic, clinical and ILD features at baseline. Pulmonary function tests (PFTs) and lung HRCT images were analysed and the extent of lung fibrosis was expressed as percentage of total lung volumes. We defined mild-moderate ILD as 1%–10% fibrosis on HRCT and severe disease as >20% fibrosis. Ground glass opacities, bronchiectasis and honeycombing were registered if present. Vital status and causes of deaths were available in all patients at study end (January 2018). Descriptive statistics and regression analysis were applied. Results: The Nor-SSc cohort included 815 patients. Baseline lung HRCT images were available in 416 patients (51%), whereof 226 (54.3%) had signs compatible with ILD. Mild to moderate ILD, defined as 1%–10% lung fibrosis were present in 149 (65.9%), while 48 (21.2%) had extensive lung fibrosis defined as >20%. Patients with mild-moderate ILD were 55.2 years at SSc onset and characterised by female gender (81.9%) and limited cutaneous SSc (70.5%). Their antibody profile was dominated by anti-centromere Ab (ACA) in 48.3%, followed by anti-polymerase III, ATA, and anti-RNP, in 14.1%, 13.4% and 5.4%, respectively. The mean modified Rodnan skin score (mRSS) was 9.3 (9.3%), baseline FVC was 93.4% and DLCO 66.5%. Univariable associations of clinical characteristics and mild-moderate ILD are shown in figure 1. After a mean observation time of 8.2 years, 49 (32.9%) of patients with mild-moderate ILD had died. The 5- and 10 year survival was 76% and 62% compared to 83% and 76% in patients with no ILD (p=0.03). In univariable cox regression analyses, mild-moderate ILD was associated with mortality (HR 1.6, 95% CI 1.03–2.40, p=0.034). Conclusions: In this population based, nationwide study, mild-moderate ILD was frequent and had a considerably impact on survival in SSc patients. Disclosure of Interest: None declared